The Influence of Differences in Income Tax Rules on Income Tax Growth in the Private Tax Taxes and Acceptance of Tax Income in the Office of Jember Pratama Tax Service - Mrenda Ayu Setyowati; Muhaimin Dimyati; Wiwik Fitrianingsih (ABM: International Journal of Administration, Business and Management, 2020)
The purpose of this study was to determine the different effects of changes in Non-Taxable Income (PTKP) regulations on the growth rate of the number of Individual Taxpayers (WPOP) and income tax article 21 (PPh 21) in the Jember KPP. The data used in this study are secondary data collected from KPP Pratama Jember period 2008-2018. Data processing methods using Descriptive Statistics, Analysis Of Variance (ANOVA) and Multivariate Analysis Of Variance (MANOVA) with SPSS analysis tool version 20. The results of the study show that there are different effects of changes in Non-Taxable Income (PTKP) significantly impacting the growth rate Personal Taxpayers (WPOP) because the rate of growth is increasing and the level of income tax article 21 (PPh 21) because the amount of revenue is increasing. Keywords: PTKP, WPOP, Income Tax 21.